The effect of brand image, brand trust and reference group on the buying decision of sneakers - Muslim, Miswanto; Mubarok, Rijal Rizki; Wijaya, Nikodemus Hans Setiadi (Goodwood Publishing, 2019)
Purpose: The purpose of conducting this study was to test the effect of brand image, brand trust, and reference group on buying decision of sneakers. Research methodology: This study took the primary data through questionnaires distribution. The analytical method used is multiple-linear regression. Results: The finding from hypothesis testing results is that brand image, brand trust, and reference group have positive effect on buying decision of sneaker shoes. Limitations: The testing involved only 3 factors, while generally, buying decision is often affected by some other factors for example, price, taste, and others. Contribution: This study can be used to add insight and reference for the next study, especially in the marketing of sneakers. Keywords: Brand image, Brand trust, Reference group, Sneakers